A Liposomal Formulation to Exploit the Bioactive Potential of an Extract from Graciano Grape Pomace - Carlos Asensio-Regalado; Rosa María Alonso-Salces; Blanca Gallo; Luis A. Berrueta; Clara Porcedda; Francesca Pintus; Antonio Vassallo; Carla Caddeo (MDPI AG, 2022)
Antioxidant compounds with health benefits can be found in food processing residues, such as grape pomace. In this study, antioxidants were identified and quantified in an extract obtained from Graciano red grape pomace via a green process. The antioxidant activity of the extract was assessed by the DPPH and FRAP tests, and the phenolic content by the Folin-Ciocalteu test. Furthermore, nanotechnologies were employed to produce a safe and effective formulation that would exploit the antioxidant potential of the extract for skin applications. Anthocyanins, flavan-3-ols and flavanols were the main constituents of the grape pomace extract. Phospholipid vesicles, namely liposomes, were prepared and characterized. Cryo-TEM images showed that the extract-loaded liposomes were predominantly spherical/elongated, small, unilamellar vesicles. Light scattering results revealed that the liposomes were small (~100 nm), homogeneously dispersed, and stable during storage. The non-toxicity of the liposomal formulation was demonstrated in vitro in skin cells, suggesting its possible safe use. These findings indicate that an extract with antioxidant properties can be obtained from food processing residues, and a liposomal formulation can be developed to exploit its bioactive value, resulting in a promising healthy product.